MicroRNAs in lung cancer: their role in tumor progression, biomarkers, diagnostic, prognostic, and therapeutic relevance - Madhura Chatterjee; Sayoni Nag; Saurabh Gupta; Tanmoy Mukherjee; Prem Shankar; Deepak Parashar; Arindam Maitra; Kaushik Das (Discover Oncology)
Abstract MicroRNAs (miRNAs) are a class of small non-coding RNAs which are associated with post-transcriptional regulation of gene expression. Dysfunction or aberrant expression of miRNAs is predominant in various malignancies including lung cancer. Lung cancer is one of the commonest causes of cancer-related death worldwide, with a five-year survival of only 10–20%. The present review summarizes the current understanding of the role of miRNAs in the development and progression of human lung cancer and their therapeutic potential. Also, we briefly discuss the canonical biogenetic pathway of miRNAs followed by a detailed illustration on how miRNAs regulate human lung cancer progression in various ways. Furthermore, we focus on how miRNAs contribute to the crosstalk between cancer cells and different cells in the tumor microenvironment in the context of lung cancer. Finally, we illustrate how different miRNAs are used as a prognostic and diagnostic biomarker for lung cancer and the ongoing miRNA-associated clinical trials. In conclusion, we discuss how targeting miRNAs can be a potential therapeutic means in the treatment of human lung cancer.